UN decade of education for sustainable development:perceptions of higher education institution’s stakeholders - Aleixo, Ana Marta (2017)
The purpose of this study is to investigate how the main stakeholders of Portuguese Higher Education Institutions (HEIs) perceive the commitment of HEIs related to: (a) teaching sustainable development Sustainable Development (SD) across all courses, (b) encouraging research and dissemination of SD knowledge, (c) implementing green campuses and supporting local sustainability efforts, and (d) engaging and sharing information with international networks (as defined in Higher Education Sustainability Initiative, United Nations). Through a qualitative approach (semi-structured interviews and content analysis), we explore the perspectives of twenty stakeholders from four Portuguese public HEIs (leaders, faculty, staff, students, and external stakeholders). The results show that all stakeholders see teaching SD across all courses as a necessity, but they have different visions about how to implement it. Concerning the research and dissemination of SD knowledge, they defend that both should be encouraged and transversal to all HEIs. About implementing green campuses and supporting local sustainability efforts, stakeholders agree that is important, but the practical results, in the Portuguese HEIs analysed, fail to achieve an acceptable degree. As a long term objective, the motivation for engaging and sharing information with international networks is latent.